2010
DOI: 10.1124/jpet.110.168880
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Selective Androgen Receptor Modulators Enhance Female Sexual Motivation

Abstract: Women experience a decline in estrogen and androgen levels after natural or surgically induced menopause, effects that are associated with a loss of sexual desire and bone mineral density. Studies in our laboratories have shown the beneficial effects of selective androgen receptor modulators (SARMs) in the treatment of osteoporosis and muscle wasting in animal models. A series of S-3-(phenoxy)-2-hydroxy-2-methyl-N-(4-cyano-3-trifluoromethyl-phenyl)-propionamide analogs was synthesized to evaluate the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…This effect of androgens should be separated from the anabolic effects on micturition, so that androgen can be used for the treatment of SUI. However, it has been reported that SARM administration induces uterus weight increase, especially in the myometrium, the smooth muscle of the uterus, but not the endometrium . Therefore, it seems that SARM treatment is less likely to affect uterine endometrium morphology compared to testosterone or DHT.…”
Section: Discussionmentioning
confidence: 96%
“…This effect of androgens should be separated from the anabolic effects on micturition, so that androgen can be used for the treatment of SUI. However, it has been reported that SARM administration induces uterus weight increase, especially in the myometrium, the smooth muscle of the uterus, but not the endometrium . Therefore, it seems that SARM treatment is less likely to affect uterine endometrium morphology compared to testosterone or DHT.…”
Section: Discussionmentioning
confidence: 96%
“…In several studies that were conducted on mice, different types of SARMs such as S-23, S-24, S-27 were found out to positively affect sexual motivation. Also, the myometrial thickness was observed to have increased with the use of different types of SARMs [33].…”
Section: Discussionmentioning
confidence: 99%
“…This is valid both for females and males because of androgen receptors [30,31,32]. According to several types of research, SARM may be used to increase sexual urges [33].…”
Section: Sexual Medicinementioning
confidence: 99%
“…anxiety, stress, breast cancer, menstrual cycle [23]- [25]. By ignoring any other unexpected factors, the drop of cortisol hormone in both genders reflects the level of stress and anxiety the student were in during the examinations.…”
Section: Discussionmentioning
confidence: 99%